Tinjauan Yuridis Tindak Pidana Ganda tentang Perempuan sebagai Korban Asusila dan Perampokan di Desa Tanjung Terang Analisis Putusan No 136/PID.B/2018/PN.MRE - Zulistian, Adi; Wardhana, Arief Wisnu; Okpriaanti , Reni (Universitas Semarang, 2025)
This research was conducted in Tanjung Terang Village, Gunung Megang District, Muara Enim Regency, South Sumatra. This research aims to analyze and explain how the law is applied to cases involving robbery and rape of women at the same time as the law for children as victims of sexual violence. (Analysis of Decision No. 136/Pid.B/2018/PN Mre) and so that it can later be implemented and useful for the interests of Law Enforcement Officials (APH) and the Community. The method used in this research is qualitative data which is descriptive, opinions and concepts as well as other explanations which are normative in nature. The type and source of data used by the author is a secondary data source which includes primary law and secondary law and the data analysis technique used in this research is the Qualitative Descriptive technique. Based on the research results, the factor that was taken into consideration by the judge in making a decision in this case was that the combined criminal act of two criminal cases, namely two criminal acts committed at the same time, were still carried out with their respective sentences, this combination is called concursus realis. That the second factor in the crime that occurred was basically the intention of the perpetrator himself accompanied by other factors, and apart from that the main factor was local security. Keywords: Multiple Crimes, Women, Immorality, Robbery